γ1-Containing GABA-A Receptors Cluster at Synapses Where they Mediate Slower Synaptic Currents than γ2-Containing GABA-A Receptors - Dixon, Christine L.; Sah, Pankaj; Keramidas, Angelo; Lynch, Joseph W.; Durisic, Nela (Frontiers in Molecular Neuroscience, 2017)
GABA-A receptors (GABAARs) are pentameric ligand-gated ion channels that are assembled mainly from α (α1-6), β (β1-3) and γ (γ1-3) subunits. Although GABAARs containing γ2L subunits mediate most of the inhibitory neurotransmission in the brain, significant expression of γ1 subunits is seen in the amygdala, pallidum and substantia nigra. However, the location and function of γ1-containing GABAARs in these regions remains unclear. In ‘artificial’ synapses, where the subunit composition of postsynaptic receptors is specifically controlled, γ1 incorporation slows the synaptic current decay rate without affecting channel deactivation, suggesting that γ1-containing receptors are not clustered and therefore activated by diffuse neurotransmitter. However, we show that γ1-containing receptors are localized at neuronal synapses and form clusters in both synaptic and extrasynaptic regions. In addition, they exhibit rapid membrane diffusion and a higher frequency of exchange between synaptic and perisynaptic populations compared to γ2L-containing GABAARs. A point mutation in the large intracellular domain and a pharmacological analysis reveal that when a single non-conserved γ2L residue is mutated to its γ1 counterpart (T349L), the synaptic current decay is slowed from γ2L- to γ1-like without changing the clustering or diffusion properties of the receptors. In addition, previous fast perfusion and single channel kinetic experiments revealed no difference in the intrinsic closing rates of γ2L- and γ1-containing receptors when expressed in HEK293 cells. These observations together with Monte Carlo simulations of synaptic function confirm that decreased clustering does not control γ1-containing GABAAR kinetics. Rather, they suggest that γ1- and γ2L-containing receptors exhibit differential synaptic current decay rates due to differential gating dynamics when localized at the synapse.